Comparability and equivalence in social research - Piovani, Juan Ignacio; Baranger, Denis (2023)
This study discusses some problematic issues around comparability and equivalence in empirical research, particularly focusing on the case of indicators and taking a cross-national study on linguistic skills and use of foreign languages in the scientific production of researchers from Argentina, Brazil, and Chile as reference. The discussion is framed within broader epistemological and methodological debates concerning the status of comparisons in the social sciences and, mainly, the case of cross-national comparative studies. Within these debates, and resorting to concrete examples arising from research into scientists' linguistics skills, we address the comparability issue of target populations and samples, as well as that of indicator equivalence, with emphasis in the problems of questionnaire design, reliability,and validity
Este artigo discute algumas questões problemáticas em torno da comparabilidade e equivalência em pesquisas empíricas, focando particularmente no caso dos indicadores, e tomando como referência um estudo transnacional sobre habilidades linguísticas e uso de línguas estrangeiras na produção científica por pesquisadores da Argentina, Brasil e Chile. A discussão se enquadra em debates epistemológicos e metodológicos mais amplos sobre o status da comparação nas ciências sociais e, principalmente, no caso dos estudos comparativos transnacionais. No âmbito destes debates, e recorrendo a exemplos concretos decorrentes da investigação das competências linguísticas dos cientistas, é abordada a questão da comparabilidade de populações-alvo e amostras, bem como da equivalência de indicadores, com destaque para os problemas de desenho de questionários, confiabilidade e validade.
Keywords: Investigación comparativa; Comparabilidad; Equivalencia; Ciencias sociales; Comparative research; Comparability; Equivalence; Cross-national studies; Pesquisa comparativa; Comparabilidade; Equivalência; Estudos transnacionais